Wages and Job Satisfaction in Portugal - José Vieira; Jo\~ao Couto; Maria Teresa Borges-Tiago (European Regional Science Association (ERSA), 2004)
The interest in the analysis of job satisfaction has increased among economists. Indeed, reported levels of satisfaction have been seen as a good predictor of individual behaviour such as job turnover, productivity and absenteeism. Because of this, several studies have tried to identify the determinants of job satisfaction. This paper is concerned with job satisfaction in Portugal. For this purpose, we use the first six waves of the European Household Panel Data (ECHP). The panel nature of the data allows us to use a random effects estimator in order to control for unobservable individual heterogeneity. The results indicate that wages matter for job satisfaction but do not tell the whole story. In particular, having a good health status, a permanent contract and working the public sector influences positively the level satisfaction. We also find a great heterogeneity in satisfaction by regions, even in a small country as Portugal. These findings are valid for overall job satisfaction as well as for satisfaction with specific job domains such as pay, security, type of work and hours worked. Key words: job satisfaction, wages, regions, unobserved heterogeneity JEL Code: J28
Keywords: J28; 330; job satisfaction; wages; regions; unobserved heterogeneity